Pengaruh Penggunaan Selebriti Dalam Iklan Terhadap Minat Beli Konsumen Dengan Citra Merek Sebagai Variabel Mediasi (Studi Kasus Iklan Shampo Pantene Versi Ralin Shah) - Lestari, Septia Dwi; Asdinardju, Asnawi (Jurnal Manajemen Bisnis, 2015)
Purpose of the research to analyze "The Effect of celebrity in advertising to consumer buying interest with brand image as mediation variabel (Study On Advertising Shampo Pantene Version Ralin Shah)". The subject of research are the students of  Universitas Muhammadiyah Yogyakarta who ever knew / saw the Pantene shampoo advertisement which starring by Raline shah. In this research, the sample are 130 respondents selected by using purposive sampling method. The collecting of sample by using purposive sampling technique. The Analysis tools are simple and multiple linear regression. Before performing data analysis, first performed instrument quality testing include validation testing and reliability testing.The results of the analysis show that the credibility, attractiveness, trustworthiness, expertise and endorse simultaneously very influential to interesting consumers, the attractiveness is important and positive effect to the brand image, the trustworthiness is important and positive effect to the brand image, the expertise is positive and significant to the brand image, the endorse is positive and significant to the image brand, brand image of the emergency against buying intention, and brand image is able to act as a mediation effect of attractiveness, trustworthiness, expertise and endorse to consumer purchase intention.